Patterns and outcomes of traumatic pancreatic injuries: A retrospective review from a large multi-institutional healthcare system. (January 2018) - Iurcotta, Toni; Addison, Poppy; Amodu, Leo I; Fatakhova, Karina; Akerman, Meredith; Galvin, Daniel; Rodriguez Rilo, Horacio L
Introduction: Traumatic pancreatic injuries are rare, and morbidity and mortality information are often conflicting. To determine the frequency and outcomes of patients presenting with trauma to the pancreas, we reviewed data from a large multi-institutional healthcare system for mechanism of injury, intervention, subsequent complications, in-hospital morbidity rates, and mortality. Methods: We performed a retrospective analysis of records of all pancreatic injury cases seen at four healthcare centers from 1990 to 2014. Descriptive measures are presented for continuous and categorical data. Mortality rates were obtained using the publicly accessible Social Security Death Master File. Results: Of 69 patients with pancreatic injuries, median age was 24 years (range 1–88). Mechanisms of injury were blunt in 87% and penetrating in 11.8%. The median injury grade was 1. Most injuries involved the pancreatic head (24.6%). Median Injury Severity Score at presentation was 9. Thirty-seven (53.6%) patients required surgery. Twenty-five patients (36.2%) required total parenteral nutrition, 34 patients (49.3%) developed intra-abdominal fluid collections, 24 patients (34.8%) developed acute pancreatitis, and three (4.4%) developed endocrine insufficiency requiring insulin. Ten (14.5%) patients died. There were four (5.8%) readmissions and one re-operation (1.4%) within 30 days of discharge. Conclusion: Traumatic pancreatic injuries occur most frequently in young healthy males with little or no comorbidities, and are generally associated with other acute injuries. Contrary to past reports, our results revealed a low mortality rate but significant morbidity, with the most common complications being intra-abdominal fluid collections, acute pancreatitis, and a need for total parenteral nutrition.